2014
DOI: 10.1088/0031-8949/89/9/095205
|View full text |Cite
|
Sign up to set email alerts
|

Properties of threshold coupled bistable maps

Abstract: In this paper we have studied the spatiotemporal behaviour of threshold coupled bistable chaotic maps. We have shown the existence of various cycles of the single map with the variation of threshold value for fixed relaxation time. The effects of variation of relaxation time on the network of threshold coupled maps are presented for different threshold values. Excess propagation through open boundaries is calculated numerically. For a network of three threshold coupled maps, the propagation of excess through o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…In Ref. [10], Nag et al studied a random threshold bistable locally coupled map and observed that the random threshold coupling can provide an annihilation method of the coexisting chaotic attractors of the locally coupled map and stabilize it to some fixed point (or periodic attractor).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In Ref. [10], Nag et al studied a random threshold bistable locally coupled map and observed that the random threshold coupling can provide an annihilation method of the coexisting chaotic attractors of the locally coupled map and stabilize it to some fixed point (or periodic attractor).…”
mentioning
confidence: 99%
“…[8], they mainly focused on the effect of noise (or random). [2][3][4][5][6][7]9,10] However, disorder is always present in the natural systems. [11] In the following we give some examples for the appearance of disorder.…”
mentioning
confidence: 99%